Pitch Channel Control of Airship with Adaptive Sliding Mode - Xinli Zhang; Yunan Hu; Baoliang Geng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Based on the nonlinear model of airship pitch channel, a kind of sliding mode control method is designed without any prior information about airship parameters. The adaptive turning law is adopted to solve the unknown information of airship in model. So the whole information for controller can used are only the measurement of pith angle and its angle speed. Detailed simulation are done for two situations such as airship flying with big trust and small trust Numerical simulation results shows that the airship can fly smooth and safe. Especially, the controller can use the same group of parameters during all kinds of above flying conditions. So it shows that the proposed method is reasonable and effective. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4754